Impact of Super-High Density Olive Orchard Management System on Soil Free-Living and Plant-Parasitic Nematodes in Central and South Italy - Silvia Landi; Giada d’Errico; Rossella Papini; Ilaria Cutino; Stefania Simoncini; Andrea Rocchini; Giorgio Brandi; Roberto Rizzo; Giovanni Gugliuzza; Giacinto Salvatore Germinara; Salvatore Nucifora; Gaetana Mazzeo; et al. (Animals, 2022)
The soil nematode community plays an important role in ecosystem services. The objective of this study was to assess the effect of Super-high density (SHD) olive orchards on the nematode community in five sites with different soils, climates, and cultivars. At each site, the SHD management system was compared to the adjacent olive orchard traditional (TRAD) system, in which the same soil management and phytosanitary measures were applied. Soil management was assessed by total organic carbon content (TOC), while the soil nematode community was evaluated using the nematode taxa abundances and soil nematode indicators. TOC was significantly decreased in the SHD olive orchard system compared to TRAD in the sites characterized by conventional tillage and mineral fertilization. The two-way ANOSIM analysis on nematode abundance showed no difference between the two olive management methods, instead showing only a significant difference per site mainly due to variabilities in plant-parasitic nematode assemblage. However, a negative impact of SHD management was evident in environments stressed by summer droughts and conventional tillage: the ratio of obligate plant-parasites to bacterivores and fungivores (Pp/(B+F)) was significantly higher in SHD than in the TRAD olive orchard system, and the prey-to-predator θ mass ratio showed the lowest values in the sites under organic fertilization or green manure. The canonical correspondence analysis showed that the free-living nematodes were only slightly affected by SHD olive orchards; instead, the presence of plant-parasitic nematodes families such as Telotylenchidae, Paratylenchidae, Meloidogynidae, and Criconematidae was favored, in comparison to Longidoridae, Heteroderidae, and Pratylenchidae.